Novell's Guide to Netware 4.01 Networks / With Fast Track Speed Notes - Currid Cheryl C; Saxon Stephen (Novell Press, 1993)
A concise, easy-to-follow guide to setting up, fine tuning, and maintaining a NetWare network. Introduction, Networks and Networking, Installing and Configuring Your NetWare Network, Creating the User Environment, Network Maintenance and Tuning, NetWare 4.0 Utilities, Dictionary of Key Concepts, What's New in NetWare 4.01, Index.